Experimental and numerical study on torsional behaviour of steel-reinforced concrete-filled square steel tubular members. (August 2021) - Shi, Yan-Li; Jia, Zhi-Lu; Wang, Wen-Da; Xian, Wei; Tan, Ee Loon
Abstract: Since steel-reinforced concrete-filled steel tubular (SRCFST) members combine the advantages of concrete-filled steel tube (CFST) and steel reinforced concrete (SRC) members, SRCFST members have been increasingly used in practical applications and may be subjected to torsion in their service life. Therefore, six square SRCFST members are designed and tested under couple compression-torsion, the main parameters include cross-section types of steel reinforced and loading paths. Subsequently, the torsional models of the SRCFST members are also established by adopting the ABAQUS. Based on experimental analysis, the core concrete damage principally appear at the upper part of the specimens. The loading paths have no obvious effect on the torsional moment-rotation angle ( T - θ ) curves of the SRCFST specimens. With the identical steel ratios of steel reinforced, specimens with internal circular steel tube bear the maximum torsional moment, and the T - θ curves of the specimens with H-section steel and cruciform steel show no significant difference. The specimens show good ductility under torsion. After the accuracy of the finite element model is verified, the influences of cross-section types of profiled steel and cross-sectional dimension of cruciform steel on torsional performance of specimens are further investigated. When the sectional dimension of the cruciform steel is larger, the steel reinforced has a significant influence on the torsional behaviour of the members. According to the testing and numerical results, a torsional formula of square SRCFST members with internal cruciform steel is proposed to predict bearing capacity.